Using Chinese word processor software in learning characters among non-native learners - Teoh, Sok Yee; Ooi, Ping Sing (2005)
Every Chinese character has it own stroke and radical and because of this, learning Chinese character has been considered by the non-native learners as the hardest learning process. The traditional method of practicing Chinese characters by hand has caused many students to lose their interest in studying the Chinese language because it is time consuming. With an advancement of technology, learning Chinese characters will not be harmful experience anymore. This paper will console the non native learners because now they need not have to learn how to write Chinese characters, they can learn the Chinese characters through the method of recognizing the characters and then writing the character by using the computer (Chinese Word Processor software). This paper will also discuss the reasons why teaching and learning Mandarin is a must in the context of UUM and suitable Chinese Word Processor software would be suggested in the learning Chinese characters.